2021
DOI: 10.1186/s13023-021-01707-6
|View full text |Cite
|
Sign up to set email alerts
|

Using pre-existing social networks to determine the burden of disease and real-life needs in rare diseases: the example of Thygeson's superficial punctate keratitis

Abstract: Background Thygeson’s superficial punctate keratitis (TSPK) is a rare and still poorly understood disease of the ocular surface, responsible for recurrent episodes of photophobia and eye pain. While TSPK is considered as a benign condition, a subset of patients has frequent recurrences or even chronic disease, two situations in which there are currently no therapeutic guidelines. We used a preexisting Facebook TSPK patient support group to assess the clinical journey and the burden of disease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…8,9 Although considered a generally benign condition, the recurrent nature of the disease, often characterized by pain and photophobia, makes TSPK a particularly distressful condition with a significant impact on quality of life. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Although considered a generally benign condition, the recurrent nature of the disease, often characterized by pain and photophobia, makes TSPK a particularly distressful condition with a significant impact on quality of life. 10…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although considered a generally benign condition, the recurrent nature of the disease, often characterized by pain and photophobia, makes TSPK a particularly distressful condition with a significant impact on quality of life. 10 The etiology of TSPK remains to be fully elucidated and several hypotheses regarding pathogenesis have been proposed over the years. Historically, the condition has been believed to be infectious in nature, given the isolation of viral particles in early reports.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study of a TSPK online community, approximately 65% of patients diagnosed with TSPK had .6 month delay after symptom onset. 57 Although largely self-resolving, the study reported that the impact on daily life was moderate for 53% of patients and 22% for severe TSPK and 80% report being deeply saddened by their eye condition. 57 TREATMENT Drug delivery is a common obstacle in the treatment of inflammatory diseases of the corneal surface.…”
Section: Differential Diagnosismentioning
confidence: 92%
“…57 Although largely self-resolving, the study reported that the impact on daily life was moderate for 53% of patients and 22% for severe TSPK and 80% report being deeply saddened by their eye condition. 57 TREATMENT Drug delivery is a common obstacle in the treatment of inflammatory diseases of the corneal surface. The tear film and epithelial surfaces are a formidable barrier for drops or ointments with poor ocular penetration.…”
Section: Differential Diagnosismentioning
confidence: 92%
See 1 more Smart Citation